The Effect of Intangible Asset On Competitive Advantage and Firm Performance; Study on Budget Accommodation in Semarang City - Armania Putri Wardhani; Amie Kusumawardhani; Muhammad Ubaidillah (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2021)
This research examines the effect of innovative capability, knowledge management and intellectual capital (intangible assets) on competitive advantage and firm performance (studies on budget accommodation in Semarang). The increasing number of hotels in Semarang city is an intriguing phenomenon; considering the background of the city itself for its lack of fame on its tourism business. However, it does not hinder investors’ intention to keep opening their businesses in the area of accommodation services. The results of the pre-research interview stated that the increasing competition made the occupancy level troubling for the accommodating service entrepreneurs, both budget accommodation and standard and upper-class hotels. This research processed 50 samples consisting of 1 - 3 star hotels, budget hotels (non-star ones) and guesthouses. The data collection method was collected by spreading out questionnaire form to the respondents. Furthermore, the data was processed using analysis tool known as Partial Least Square (PLS). This study concludes that innovative capability, knowledge management, and intellectual capital which are part of the intangible assets of the firm have a positive effect on competitive advantage. Furthermore, competitive advantage also has a positive influence on firm performance. This study provides managerial implications that budget accommodation service entrepreneurs are able to improve their competitive advantage and firm performance through understanding and managing their intangible assets.Keywords: firm performance, competitive advantage, innovative capability, knowledge management, intellectual capital. AbstrakPenelitian ini menguji pengaruh kapabilitas inovatif, manajemen pengetahuan dan modal intelektual (aset tidak berwujud) terhadap keunggulan kompetitif dan kinerja perusahaan (studi tentang akomodasi anggaran di Semarang). Meningkatnya jumlah hotel di kota Semarang merupakan fenomena yang menggelitik; mengingat latar belakang kota itu sendiri karena kurangnya ketenaran pada bisnis pariwisatanya. Namun hal tersebut tidak menghalangi niat investor untuk tetap membuka usahanya di bidang jasa akomodasi. Hasil wawancara pra penelitian menyatakan bahwa persaingan yang semakin ketat membuat tingkat hunian semakin meresahkan pengusaha jasa akomodatif, baik akomodasi budget maupun hotel standar dan kelas atas. Penelitian ini mengolah 50 sampel yang terdiri dari hotel bintang 1 - 3, hotel melati (non bintang) dan losmen. Metode pengumpulan data dilakukan dengan menyebarkan kuesioner kepada responden. Selanjutnya data diolah dengan menggunakan alat analisis yang dikenal dengan Partial Least Square (PLS). Penelitian ini menyimpulkan bahwa kapabilitas inovatif, manajemen pengetahuan, dan modal intelektual yang merupakan bagian dari aset tak berwujud perusahaan berpengaruh positif terhadap keunggulan bersaing. Keunggulan bersaing juga berpengaruh positif terhadap kinerja perusahaan. Studi ini memberikan implikasi manajerial bahwa pengusaha jasa akomodasi anggaran mampu meningkatkan keunggulan kompetitif dan kinerja perusahaan melalui pemahaman dan pengelolaan aset tidak berwujud mereka.Kata Kunci: Kinerja perusahaan; Keunggulan bersaing; Kapabilitas inovatif; Manajemen pengetahuan; Modal intelektual